Evaluation of Technical and Cultural Barriers to Digital Accounting System Implementation in Modern Organizations - Halim, Prihartono Aksan (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This research evaluates modern organizations' technical and cultural barriers to implementing digital accounting systems. It seeks to identify how these barriers interact and influence the overall effectiveness of digital transformation efforts in accounting. A systematic literature review synthesized existing research on the subject, focusing on peer-reviewed articles published in 2014. The study incorporated diverse perspectives to understand the challenges organizations encounter comprehensively. The findings reveal significant technical barriers, including inadequate technological infrastructure and challenges in integrating legacy systems with new technologies. Cultural barriers, particularly employee resistance and conservative organizational culture, further complicate the adoption process. The interaction between these barriers underscores the need for a holistic approach to digital transformation. This study contributes original insights to the field of digital transformation in accounting, emphasizing the importance of addressing both technical and cultural aspects for successful implementation. Organizations should invest in technological upgrades while fostering a culture that supports innovation and change. Management should prioritize leadership engagement and employee involvement to facilitate smoother transitions to digital accounting systems.